Hemodynamic Surveillance of Unilateral Carotid Artery Stenting in Patients With or Without Contralateral Carotid Occlusion by TCD/TCCD in the Early Stage Following Procedure - Yan, Ziguang; Yang, Min; Niu, Guochen; Zhang, Bihui; Tong, Xiaoqiang; Guo, Hongjie; Zou, Yinghua (Frontiers in Neurology, 2019)
Objective: To evaluate the cerebral hemodynamic variations in patients with unilateral carotid artery stenosis and contralateral carotid occlusion(CCO) in hours following carotid artery stenting (CAS) by transcranial Doppler(TCD) or transcranial color-code Doppler(TCCD). Methods: 65 consecutive patients who underwent unilateral CAS were enrolled. Among them, 14 patients had ipsilateral severe stenosis and CCO (CCO group) while the other 51 patients had only unilateral severe carotid stenosis without CCO (UCS group). All patients underwent TCD or TCCD monitoring before, at 1hr and 3hr after CAS. We monitored bilateral middle cerebral artery(MCA) peak systolic velocity (PSV), pulsatility index (PI), and blood pressure (BP), and compared that data between two groups. Results: In UCS group, ipsilateral MCA PSV increased relative to baseline at 1hr (96 ± 30 vs. 85 ± 26 cm/s, 15%, P < 0.001) and 3hr (97 ± 29 vs. 85 ± 26 cm/s, 17%, P < 0.001) following CAS. Significant PI increases were observed at 1hr and 3hr following CAS on the ipsilateral side. In CCO group, ipsilateral MCA PSV increased relative to baseline at 1hr (111 ± 30 vs. 83 ± 26 cm/s, 35%, P < 0.001) and 3hr (107 ± 28 vs. 83 ± 26 cm/s, 32%, P < .001) following CAS. The magnitude of ipsilateral MCA PSV increase was significantly higher in CCO group compared with UCS group at 1hr (P = 0.002) and 3hr (P = 0.024) following CAS, while BP similarly decreased between the two groups. On the contralateral side, significant MCA PSV increases were observed following CAS in CCO group but not in UCS group. Bilateral MCA PSV increases were higher in patients with a stenosis degree of ≥ 90% than in patients with stenosis degree of 70-89% only in CCO group. Conclusion: The ipsilateral MCA PSV and PI increase moderately in the initial hours after unilateral CAS in patients without CCO. In patients with CCO, the ipsilateral and contralateral MCA PSV increase significantly in the early stage following CAS. CCO is a factor of the increased blood flow velocity in ipsilateral MCA after unilateral CAS.